Types of fish caught with beach seine gear in Gampong Pulot, Leupung District, Aceh Besar - Pandang, Ivonda Vicana; Chaliluddin, Chaliluddin; Mardhatillah, Inda; Fadia, Aqilla (Depik Jurnal Ilmu Ilmu Perairan, Pesisir, dan Perikanan, 2025)
Coastal fisheries play a vital role in supporting food security and livelihoods in Aceh, Indonesia. Among the various fishing methods used by artisanal fishers, the beach seine remains one of the most traditional and culturally significant gears, passed down through generations and still widely practiced in Gampong Pulot, Leupung District, Aceh Besar. Despite its importance, studies on the species composition and ecological implications of beach seine operations in this area remain limited. This study aimed to identify the types of fish caught using beach seine gear and analyze their composition to better understand the ecological characteristics of the catch. The research was conducted from January to March 2025 using a survey method, collecting both primary and secondary data through field observations and literature review. Results showed a total catch of 2,926.5 kg, comprising 16 fish species. The dominant species were bluefin trevally (Caranx melampygus, 28.43%), anchovy (Stolephorus indicus, 22.66%), and yellowtail scad (Carangoides ciliaris, 19.55%). The findings indicate that the beach seine fishery in Gampong Pulot mainly targets schooling pelagic species, which are ecologically important and economically valuable. These results highlight the need for sustainable management strategies to ensure the long-term viability of traditional fisheries and the protection of coastal ecosystems.Keywords:Aceh coastal communitiesArtisanal fisheriesBeach seine fisheryCatch compositionTraditional fishing gear